# |
ODE |
Mathematica |
Maple |
\[
{}y = t \left (2-y^{\prime }\right )+2 {y^{\prime }}^{2}+1
\] |
✓ |
✓ |
|
\[
{}y = t y^{\prime }+3 {y^{\prime }}^{4}
\] |
✓ |
✓ |
|
\[
{}y-t y^{\prime } = -2 {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y-t y^{\prime } = -4 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{\prime }} = 1
\] |
✓ |
✓ |
|
\[
{}\sin \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}\ln \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}\tan \left (y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y^{\prime }} = x
\] |
✓ |
✓ |
|
\[
{}\tan \left (y^{\prime }\right ) = x
\] |
✓ |
✓ |
|
\[
{}4 {y^{\prime }}^{2}-9 x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 y y^{\prime } = y^{2} \left ({\mathrm e}^{2 x}-1\right )
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 x y^{\prime }-8 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}+3 x y y^{\prime }+2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-\left (y+2 x \right ) y^{\prime }+x^{2}+x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+\left (x +2\right ) {\mathrm e}^{y} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = y {y^{\prime }}^{2}-x^{2} y^{\prime }+x^{2} y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y y^{\prime }+{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-4 x y^{\prime }+2 y+2 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2} {\mathrm e}^{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{\frac {y^{\prime }}{y}}
\] |
✓ |
✓ |
|
\[
{}x = \ln \left (y^{\prime }\right )+\sin \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x = {y^{\prime }}^{2}-2 y^{\prime }+2
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } \ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = \left (y^{\prime }-1\right ) {\mathrm e}^{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2} = {\mathrm e}^{\frac {1}{y^{\prime }}}
\] |
✓ |
✓ |
|
\[
{}x \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} = a
\] |
✓ |
✓ |
|
\[
{}y^{{2}/{5}}+{y^{\prime }}^{{2}/{5}} = a^{{2}/{5}}
\] |
✓ |
✓ |
|
\[
{}x = y^{\prime }+\sin \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } \left (1+y^{\prime } \cos \left (y^{\prime }\right )\right )
\] |
✓ |
✓ |
|
\[
{}y = \arcsin \left (y^{\prime }\right )+\ln \left (1+{y^{\prime }}^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+\ln \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = \left (1+y^{\prime }\right ) x +{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+\sin \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}-\frac {1}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = \frac {3 x y^{\prime }}{2}+{\mathrm e}^{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {a}{{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-y y^{\prime }-y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+a \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}x = \frac {y}{y^{\prime }}+\frac {1}{{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (1+{y^{\prime }}^{2}\right )-4 y y^{\prime }-4 x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-4 y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }+y\right )^{2}+3 x^{5} \left (x y^{\prime }-2 y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \left (y-2 x y^{\prime }\right )^{2} = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}8 {y^{\prime }}^{3}-12 {y^{\prime }}^{2} = 27 y-27 x
\] |
✗ |
✓ |
|
\[
{}\left (y^{\prime }-1\right )^{2} = y^{2}
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2}-x y^{\prime }+x
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }+y\right )^{2} = y^{\prime } y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}+y^{2} = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y y^{\prime }+{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}3 x {y^{\prime }}^{2}-6 y y^{\prime }+x +2 y = 0
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {a^{2} {y^{\prime }}^{2}+b^{2}}
\] |
✓ |
✓ |
|
\[
{}4 x^{2} {y^{\prime }}^{2}-y^{2} = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x {y^{\prime }}^{2}-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4} = 1
\] |
✓ |
✓ |
|
\[
{}x y = y^{\prime } \ln \left (\frac {y^{\prime }}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}+y^{\prime } \left (x -y\right )-x = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+y^{2} = x^{2} y^{2}+x^{4}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (y^{2}+x y+x^{2}\right ) {y^{\prime }}^{2}+\left (x y^{3}+x^{2} y^{2}+x^{3} y\right ) y^{\prime }-x^{3} y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3} = 1+y^{\prime }
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-x^{3} \left (1-y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+y^{3}-3 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2} {\mathrm e}^{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (y^{\prime }-1\right ) = \left (2-y^{\prime }\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y \left (1+{y^{\prime }}^{2}\right ) = 2 \alpha
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4} = 4 y \left (x y^{\prime }-2 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+\frac {x^{2}}{2}+{y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}y = \frac {k \left (x +y y^{\prime }\right )}{\sqrt {1+{y^{\prime }}^{2}}}
\] |
✗ |
✓ |
|
\[
{}x = y y^{\prime }+a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x {y^{\prime }}^{2}+{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (x^{2}-1\right )-2 x y y^{\prime }+y^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (y^{\prime }-1\right ) = \left (2-y^{\prime }\right )^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4} = 4 y \left (x y^{\prime }-2 y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}y = {y^{\prime }}^{2}-x y^{\prime }+\frac {x^{3}}{2}
\] |
✗ |
✗ |
|
\[
{}y = 2 x y^{\prime }+\frac {x^{2}}{2}+{y^{\prime }}^{2}
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{2}-y y^{\prime }+{\mathrm e}^{x} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+2 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 {y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{z -y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (x^{2}-1\right ) = 1
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+v^{\prime }} = \frac {{\mathrm e}^{u}}{2}
\] |
✓ |
✓ |
|
\[
{}4 {y^{\prime }}^{3} y-2 x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }+x^{3} = 16 y^{2}
\] |
✓ |
✗ |
|
\[
{}y = x y^{\prime }+y^{\prime }-{y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y-2 x y^{\prime }-y {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x = {y^{\prime }}^{2}+y
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x {y^{\prime }}^{2}-y^{2} {y^{\prime }}^{2}-2 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|